Contrast-Enhanced Ultrasound (CEUS) in the Diagnostic Algorithm of Hepatocellular and Cholangiocellular Carcinoma, Comments on the AASLD Guidelines - Dietrich, C. F.; Cui, X. W.; Boozari, B.; Hocke, M.; Ignee, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Contrast-enhanced ultrasound (CEUS) has long been present in important guidelines and recommendations for the diagnostic work-up of focal liver lesions in patients with cirrhosis. These guidelines have included the guidelines of the American Association for the Study of Liver Diseases (AASLD) 2005, the Asian Pacific Association for the Study of the Liver consensus recommendations on hepatocellular carcinoma, the recommendations of the Japanese Society of Hepatology, and the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) guidelines 2004, 2008 and 2012 (in preparation). Recently, the AASLD removed CEUS from their guidelines in part because of the perceived possibility of false-positive hepatocellular carcinoma (HCC) diagnosis in patients with intrahepatic cholangiocarcinoma (ICC), and in part because CEUS is not available in the USA. This latter factor means that published results are not entirely applicable to a North American population. The present manuscript discusses the diagnostic algorithm of hepatocellular carcinoma and provides information on the differential diagnosis between HCC and ICC.
Keywords: diagnosis; characterization; metastases; liver tumor; focal nodular hyperplasia; hemangioma